Perancangan Aplikasi Pengendalian Ruang Kelas Berbasis Mobile - Dian Hartanti; Bayu Pratama; Dwipa Handayani (Journal of Informatic and Information Security, 2021)
Classrooms are an inseparable part of course scheduling, because every lecture schedule arrangement Lecturers definitely need a classroom to teach these courses, currently the study program secretary still uses Microsoft Excel to arrange classrooms, this causes difficult problems to manage lecture schedule. and classrooms so as not to clash due to class limitations, therefore an application is made to facilitate control of classrooms both class scheduling and class replacement. It is hoped that this application can simplify the work of all parties.